Análisis de la gestión de cobro de los impuestos prediales administrados por el Gobierno Autónomo Descentralizado Municipal del cantón Manta - Anzules Marcillo, Erick Gregorio (2025)
The research analyzed the management of property tax collection administered by the Decentralized Autonomous Government (GAD) of the municipality of Manta, during the period 2019–2023. This study arose from the need to improve collection mechanisms, considering that these taxes constitute an essential source of income for local governments, impacting the administration of community services. It was a bibliographic and field-based investigation, where the applied methods were inductive–deductive and analytical–synthetic. For this purpose, a mixed-methods approach was employed, applying surveys to public servants from the Treasury, Coactive Collection, and Revenue departments, as well as interviews with GAD authorities such as the mayor and the Head of Coactive Collection. The findings revealed various weaknesses in the collection process, such as outdated municipal cadaster records, deficiencies in notification methods to delinquent taxpayers, and a low tax culture among the population. Based on this diagnosis, an improvement plan was formulated that included strategies such as the digital update of the cadaster, staff training, tax awareness campaigns, and the incorporation of technological tools to streamline collection. These proposals were aimed at increasing the efficiency of the collection process and strengthening the financial autonomy of the GAD. In conclusion, it was determined that effective tax management not only increases municipal revenue but also fosters greater civic responsibility and strengthens institutional transparency. The implementation of these strategies would represent a positive transformation in the fiscal administration of the municipality of Manta.